Prediction of Transformer Age Based on Temperature Due to Loading Using Linear Trend Method: Case Study of 60 MVA Transformer - Widagdo, Reza Sarwo; Slamet, Puji; Ubaidillah, Muhammad (Politeknik Negeri Batam, 2024)
Power Transformers are one of the core equipment found in substations. Every year the need for electricity increases, so that the transformer can work optimally, the loading must also be considered. According to IEC 354, if the transformer is underload it is 100% stable at conditions around 20℃ and the winding temperature is 98℃, but if the ambient temperature is more than 20℃ then the life of the transformer will be reduced. In this research, the loading data used is a 60 MVA power transformer for 2020-2022, specifically to predict the age of the transformer from the load increase factor in the coming year using the linear trend method. The linear trend method aims to predict the burden in the following year and every year the burden increases. an increase of 2%. To find out the results of load forecasting, the prediction in 2030 has a life loss value of 1.2 p.u or the estimated remaining life of the power transformer is 1 year 6 months with a load of 88.64%.